Improving didactic support for the development of project competence in future teachers - Israilov Khamidjon Israilovich (Zien Journals, 2024)
This article describes the project competencies of a future teacher and its characteristics, essence, abilities of subjects of the educational process applied with modern technologies, project skills and abilities for creating integrated projects, the use of organized project activities to solve problems of professional growth and development in future teachers, as well as what competencies a modern teacher should have. Scientific and methodological recommendations are given for improving the project skills of future teachers.
Keywords: Educational process; future taechar; competences